Study of the Relationship between Interleukin 17 Levels and Iron Status in Patients with Chronic Myeloid Leukemia - Al-Khaffaf, Walid Abdul Ali (Journal of Science in Medicine and Life, 2025)
Leukemia is one of the most dangerous diseases. It is an abnormal growth of blood-forming stem cells. The bone marrow normally produces many blood cells that do not function normally. The aim of this study was to investigate the relationship between interleukin 17 (IL-17) and iron levels in patients with chronic myeloid leukemia (CML). The study period was from February 25, 2023 to February 5, 2025, and it was conducted at Al-Sadr Medical City in Najaf, Iraq. A blood sample was taken, and iron levels were measured. Serum was also taken from the patients to measure IL-17 levels. The number of patients was 60, and the results were compared with 30 individuals who were considered a control group. The results showed a significant decrease (P < 0.05) in iron levels in blood patients. However, the opposite was true for CML patients, who were significantly lower in IL-17 levels when compared to the control group. The study results indicate a close correlation between iron status and interleukin 17 (IL-17) levels in patients with chronic myelogenous leukemia (CML). Iron metabolism and inflammatory pathways mediated by IL-17 may be indicative of the disease and its health status in CML. These two markers can be used as biomarkers for further study and treatment.